O texto de biologia do livro didático de ciências - Selma Ambrozina de Moura Braga (2003)
This study reports the analysis of verbal text on biology topics in science textbooks for 5th through 8th grade. I examined two series of textbooks, which were recommended by the Textbook National Program of the Brazilian Education Ministry - PNLD/MEC. In Brazil, verbal texts have received little attention in educational research on science textbooks, hence, our decision to adopt this approach. Among the few studies on science textbooks, many consider only the inappropriateness of textbooks for the goals of schooling. Consequently, these studies tend to focus on issues such as the conceptions about the nature of science present in textbooks, the discriminatory ways in which certain groups of the society are portrayed in textbooks, how the subject matter knowledge is decontextulized and out of date; and the absence of experimental activities combined to the prevalence of activities involving only memorization and the application of formulas. In the present research, I adopt a different perspective, informed by studies in the field of language. Thus, the goal is to investigate the text on biology in textbooks highlighting the relationships between linguistic aspects of the verbal text and their conditions of production. The analysis is based on Bakhtins work on speech genres, considering the thematic, compositional, and stylistic features of utterances. This broad perspective frames the use of categories proposed by Bronckart, Halliday, Martin and Mortimer. Based on the systematization of the results of this research, I argue that these texts represent a particular discourse genre which is structured around the relationships between its conditions of production and the hybridization of elements from multiple speech genres, namely the scientific, the didactic, and the day-to-day speech genres. The study of text in science textbooks, adopting this perspective, appears to be very significant for understanding the textbooks and their roles in science teaching and learning, as well as science teacher professional development.